A Case Study of ROI in Organizational Performance of Working at Home. Issue 4 (17th January 2013) - Phillips, Jack; Phillips, Patti; Robinson, Rachel
Abstract With the growing suburban population, many employees in metro areas are facing long commutes to and from the workplace. According to the 2011 Texas Transportation Institute's Urban Mobility Report, the average commuter experiences 34 hours of delay per year and spends an extra $713 on fuel (see http://tti.tamu.edu/documents/mobility‐report‐2011.pdf). This not only causes stress for the employee but also has a serious impact on the organization and the environment.